A comparative study of frictional response of shed snakeskin and human skin - Abdel-Aal, H.A.; El Mansori, M.; Zahouani, H. (Wear, 2017)
Skin in biological systems, including humans, perform several synchronized tasks (mechanical, protective, tactile, sensory, etc.). Tribological function is among skin tasks and may determine the survivability of many species. Cross comparison of tribological functional traits of skin of different species, albeit interesting, is rarely encountered, if at all exists, in tribology literature. One interesting example is that of snake and human skins. This skin pair was the subject of many studies for transdermal drug delivery. Results in that context concluded that snakeskin is highly compatible with human skin despite apparent differences in surface structure and topology. The reported compatibility raises curious question of whether there exists frictional or tribological compatibility between the two skins and if so, under what conditions, and which context. In this work, we report, for the first time in open literature, results of a comprehensive comparative investigation of shed snakeskin and human skin with respect to tribological behaviour. To this end, we compared the frictional response of shed skin obtained from P. regius and human skin from different anatomical sites, gender, and age. The results imply that, in essence, the mechanisms governing the friction response of human skin are common to snake skin despite difference in chemical composition and apparent surface structure. In particular, both skin types display sensitivity to hysteresis and adhesive dissipation. Human skin, however, being more sensitive to hysteresis than snakeskin. One interesting finding of the study is that the ratio of the coefficients of friction for snake and human skin, when sliding on the same interface, depends on the reciprocal of their respective moduli of elasticity. •We investigate similarity in friction of human and reptilian skin.•We compare measurements of COF for each skin type.•A model to compare the COF was developed.•Ratio of COF is proportional to the ratio of Elastic Moduli.•Similarity in friction originates from similarity in tensile behavior.